The alleviating effect of Scutellaria amoena extract on the regulation of gut microbiota and its metabolites in NASH rats by inhibiting the NLRP3/ASC/caspase-1 axis - Lin, Yu-Ping; Fang, Qiong-Lian; Fu, Sheng-Nan; Li, Xin-Ping; Shi, Rui; Du, Cheng-Hong; Qiao, Xue; Yin, Xun-Qing; Zeng, Yong-Cheng; Zhao, Xiu-Juan; Hua, Yan (Frontiers in Pharmacology, 2023)
Background: Scutellaria amoena (SA) is the root of Scutellaria amoena C.H. Wright of Labiatae, also known as Scutellaria southwestern. This is mainly distributed in Sichuan, Yunnan, and Guizhou in China. In southwest China, SA is used as an alternative method to genuine medicine for the treatment of allergy, diarrhea, inflammation, hepatitis, and bronchitis. Thus far, studies on the effects of SA on non-alcoholic steatohepatitis (NASH) are lacking. This paper investigated the effect of SA on the regulation of gut microbiota and its metabolites in NASH rats by inhibiting the NOD-like receptor 3 (NLRP3)/ apoptosis-associated speck-like protein (ASC)/caspase-1 axis.Methods: A NASH rat model was induced by a high-fat diet (HFD) for 12 weeks, and rats were orally given different doses of SA extracts (150 and 300 mg/kg/d) for 6 weeks. Changes in histological parameters, body weight, organ indexes, cytokines, and biochemical parameters related to NLRP3 in NASH rats were checked. 16S rRNA gene sequencing and UPLC-MS/MS technology were used to analyze the changes in the gut microbiota composition and its metabolites in NASH rats.Results: SA significantly inhibited the HFD-induced increase in body weight, lipid levels, and inflammatory infiltration. SA notably inhibited the HFD-induced increase in the upper and lower factors of NLRP3, such as transforming growth factor (TGF)-β, tumor necrosis factor (TNF)-α, interleukin (IL)-6, IL-18, pro-IL-18, IL-1β, pro-IL-1β, NLRP3, ASC, and caspase-1. Additionally, mRNA expressions of caspase-1, NLRP3, and ASC were significantly down-regulated after SA treatment. The results of the intestinal flora showed that SA could increase the diversity of flora and change its structure and composition in NASH rats by reducing Firmicutes/Bacteroidetes (F/B) ratio, Blautia (genus), Lachospiraceae (family), and Christensenellaceae R-7 group (genus), and increasing Muribaculaceae (family) and Bacteroides (genus). The metabolomics revealed that 24 metabolites were possibly the key metabolites for SA to regulate the metabolic balance of NASH rats, including chenodeoxycholic acid, xanthine, and 9-OxoODE. Nine metabolic pathways were identified, including primary bile acid biosynthesis, bile secretion, purine metabolism, and secondary bile acid biosynthesis.SA can regulate the intestinal microbial balance and metabolic disorder by inhibiting the NLRP3/ASC/caspase-1 axis to relieve NASH.